Novel Glycolipids Synthesized Using Plant Essential Oils and Their Application in Quorum Sensing Inhibition and as Antibiofilm Agents - Ruchira Mukherji; Asmita Prabhune (The Scientific World Journal)
Essential oils (EOs) form an important part of traditional medicine so their anti-microbial and, in the recent past, antiquorum sensing activity has been well studied. However it is likely that due to their hydrophobic nature and reduced solubility in aqueous environments full potential of their activity cannot be realized. hence it is only rational to formulate a process to make these molecules more polar in nature. The present paper reports synthesis of sophorolipids using 12 different essential oils as substrates, thus providing surfactant-like properties to these EOs. The synthesis protocol makes the use of Candida bombicola ATCC 22214 as producer organism. The production process required 7 days of incubation at 28°C and 180 rpm. Preliminary characterization of the synthesized essential oil sophorolipids (EOSLs) was performed using thin layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR). Additionally, essential oils that were incapable of mediating quorum sensing inhibition (QSI) on their own became potent quorum sensing inhibitors upon conversion into their corresponding EOSLs. Antibiofilm potential of these EOSLs was also demonstrated using V. cholerae as test organism. Use of essential oils as substrates for glycolipid synthesis has not been attempted previously, and hence this is the first report.